Comparison of effectiveness of 7.5% Povidone-iodine with 1% Clotrimazole ear drops and lignocaine in Otomycosis - Tabassum Aziz , Nousheen Qureshi , Mahwash Khawaja , Rida Ulfat , Tahir Muhammad , Anum Malik , Tabassum Aziz , Nousheen Qureshi , Mahwash Khawaja , Rida Ulfat , Tahir Muhammad , Anum Malik (Journal of Rawalpindi Medical College, 2020)
Objectives: Our study is comparing the effectiveness of 7.5% Povidone-iodine with 1% Clotrimazole ear drops and lignocaine in the management of Otomycosis to highlight the importance of replacing conventional antifungals in routine practice. Setting: Department of ENT and Head and Neck Surgery, Holy Family Hospital, Rawalpindi, Pakistan. Study design: A prospective randomized control trial Methodology: This study was conducted for 12 months in our institute from July 2014 to June 2015. A total number of 148 patients with clinically diagnosed Otomycosis between the age group 15 to 55 years were studied. All patients with a clinical diagnosis of Otomycosis presenting with all four features of earache, itching, ear-blockage, and ear discharge in ENT OPD were included. Ear swabs were taken and sent for fungal culture. Patients were divided into A and B groups each comprising of 74 patients. Group A received 1% Clotrimazole ear drops and lignocaine and group B received 7.5% Povidone-iodine for 14 days after the results of cultures were received. At the end of 14 days, patients of both groups were compared based on the resolution of symptoms and signs. Results: At the end of 14 days, 32 out of 74 patients (43%) in group A receiving 1% Clotrimazole ear drops and lignocaine reported resolution of all symptoms, and 52 out of 74 patients(70%) showed complete resolution of all signs, while in group B,68 out of 74 patients(91%) showed complete resolution of symptoms and 69 out of 74 patients (93%) showed complete resolution of signs. Our study showed significant improvement in signs and symptoms of Otomycosis achieved by treatment with 7.5% Povidone-iodine compared to that achieved by 1% Clotrimazole ear drops and lignocaine. Conclusion: 7.5% Povidone-iodine is a more effective antifungal agent in the treatment of Otomycosis as compared to 1% Clotrimazole ear drops and lignocaine.